2016
DOI: 10.1093/abbs/gmw075
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal domains of ARC1 are essential for interaction with the N-terminal region of Exo70A1 in transducing self-incompatibility of <italic>Brassica oleracea</italic>

Abstract: Self-incompatibility (SI) is an important mating system to prevent inbreeding and promote outcrossing. ARC1 and Exo70A1 function as the downstream targets of the S-locus receptor kinase and play conservative roles in Brassica SI signaling. Based on the sequence homology, Exo70A1 is divided into four subdomains: leucine zipper (Leu are required for the interaction with Exo70A1, while the addition of ARM motif results in loss of the interaction with Exo70A1. Meanwhile, the N-terminal of Exo70A1 without any dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…Further analysis showed that EbARC1 interacted with Exo70A1 ( Figure 6). The same study in Brassica also indicated that ARC1 interacts with Exo70A1, and the ARC1-Ubox domain and the N-terminal of Exo70A1 are the key regions for the interaction [16,39,40], which is consistent with our results ( Figure 6). Exo70A1 is a compatibility factor that is required for normal germination and growth of pollen [41].…”
Section: Discussionsupporting
confidence: 92%
“…Further analysis showed that EbARC1 interacted with Exo70A1 ( Figure 6). The same study in Brassica also indicated that ARC1 interacts with Exo70A1, and the ARC1-Ubox domain and the N-terminal of Exo70A1 are the key regions for the interaction [16,39,40], which is consistent with our results ( Figure 6). Exo70A1 is a compatibility factor that is required for normal germination and growth of pollen [41].…”
Section: Discussionsupporting
confidence: 92%
“…Before pollination, the expression of the SRK and arm repeat containing 1 (ARC1), an E3 ubiquitin ligase, were suppressed in the Bnamlpk quadruple mutant disrupting SI signal transduction to enable pollen tube growth and elongation. Both MLPK and ARM1 are positive regulators that are known to interact with SRK in the SI pathway (Shi et al 2016). By comparison, the self-compatible factor GLO1 was slightly induced in the Bnamlpk quadruple mutant (Chen et al 2019).…”
Section: Introductionmentioning
confidence: 99%